PDF Based Icing Image Recognition Applied to Online Early Warning System for Transmission Lines - Xin Yin; Xu Chen; Ertao Lei; Minghao Wen (Institute of Advanced Engineering and Science, 2015)
This paper proposes an online early warning technique and the probability distribution function based icing image recogition for overhead power transmission lines. The main functionality of the online early warning of icing, forest fire,lighting, insulator flashover, conductor gallopiong and invasion which is based on a scheme of the online inspection system for the transmission lines with optical fibre communication technology. As a case study, the early warning of icing is discussed in this paper and a comprehensive icing early warning scheme has been proposed: the local meteorological conditions and mechanical data are applied for the initial criteria of the icing early warning system, and the PDF based image recognition technology is then used to finally decide the icing condition of transmission lines, which can be mor effectively dealt with than complex pictures acquired at towers. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7210